Anycasting in connection - oriented computer networks: models, algorithms and results - Walkowiak, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Our discussion in this article centers around various issues related to the use of anycasting in connection-oriented computer networks. Anycast is defined as a "one-to-one-of-many" transmission to deliver a packet to one of many hosts. Anycasting can be applied if the same content is replicated over many locations in the network. Examples of network techniques that apply anycasting are Content Delivery Networks (CDNs), Domain Name Service (DNS), Peer-to-Peer (P2P) systems
Keywords: anycasting; connection-oriented networks; optimization; MPLS; survivability